A proof of concept to differentiate among differences in flavor of American lamb using volatile flavor compound analysis - Isaacs, Karissa Ann, author; Woerner, Dale R., advisor; Belk, Keith E., advisor; Tatum, J. Daryl, committee member; LeValley, Stephen B., committee member; Heuberger, Adam L., committee member; Meiman, Paul, committee member (Colorado State University. Libraries, 2023)
Experiments were conducted on lamb legs (n=25 per treatment) from 3 dentition groups [ young lambs (0 permanent incisors), yearlings (2 permanent incisors) and mature sheep or mutton (>2 permanent incisors)] to establish a proof of concept for differentiating the inherent differences in flavor that exist in meat from ovine animals of various age classes using volatile flavor compound analysis. The legs were selected from commercial processing facilities. Differences among age group, breed type, sex and production background were evaluated for sensory analysis and volatile compound analysis. Trained panelists evaluated ground meat patties from each leg for lamb flavor intensity and off flavor intensity. In addition, samples were analyzed to determine percentages of lipid, moisture, protein, and ash as well as to identify volatiles produced during cooking of a raw composite of lean and fat from the external surface of the leg. Analysis of variance was conducted for sensory flavor attributes relative to animal age and production background (grain vs grass) helped to describe the experimental samples. Ratings for lamb flavor intensity were higher (P < 0.05) for lamb carcass samples than for yearling carcass samples, and lamb flavor intensity scores were similar for lamb and mature age classes. Off-flavor intensity ratings were highest (P < 0.05) for samples from mature lamb carcasses, while lamb and yearling samples produced the lowest (P < 0.05) off-flavor intensity ratings. Lamb flavor intensity and off-flavor intensity ratings were higher (P < 0.05) for grass-fed lamb samples compared to grain-fed lamb samples. Mature samples had the greatest (P < 0.05) off-flavor intensity, while lamb and yearling samples had the least (P < 0.05) off-flavor intensity. Grass-fed lamb samples had the higher (P < 0.05) lamb flavor intensity scores and higher (P < 0.05) off-flavor intensity scores. Correlations between sensory attributes and metabolites helped to narrow the 500+ to 50 of significance. Findings indicated that metabolites (volatile compounds) were related to flavor of sheep meat. Finally, regression techniques helped to predict lamb flavor intensity, off flavor intensity and proof-of-concept for classifying lamb flavor.
Keywords: lamb flavor